Pengukuran Resiliensi Latihan Siswa Ekstrakurikuler Bola Voli SMA Muhammadiyah Makarti Jaya Tahun Ajaran 2023/2024 - Bayu Asromo; Siti Ayu Risma Putri; Hengki Kumbara (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
The purpose of the study was to determine how much the resilience of volleyball extracurricular student training at SMA Muhammadiyah Makarti Jaya in the 2023/2024 school year. The research method uses a survey method with a single variable type. The population in the resilience study amounted to 15 female students in volleyball extracurricular activities and the sample was taken from a total population of 15 female students. Data collection techniques using online questionnaire distribution using Google Form. The reliability value of the questionnaire based on resilience indicators including emotion regulation (0.8422) with a total of 9 items, impulse control (0.8066) with a total of 6 items, optimism (0.8066) with a total of 5 items, and self-efficacy (0.7090) with a total of 5 items, The data grouping analysis technique uses a Likert scale. The results of the study are in accordance with the indicators that the average athlete who has good emotional regulation in extracurricular activities is 36.33 (46%) with good criteria. The average athlete's ability to impulse control is 24.73 (53%) with very good criteria. The average athlete's ability to deal with optimism during training is 23.53 (47%) with good criteria. The average athlete's ability to solve self-efficacy problems during training is 16.46 (33%) with good criteria. In the overall answer of the student group, the results of the Interval value of all students' answers were 33% very good, 33% good, and 33% of students' answers were sufficient. The validity hypothesis test shows the results with a significant level of 5%, therefore getting the results of r count> r table with r table 0.553 with a valid statement. Based on data analysis and discussion of the research results, it can be concluded that there are student resilience disorders that are in accordance with the indicators of each question item given to students who experience resilience disorders. The majority of students with low resilience levels will show answers that match what is inside the student according to the wishes of the heart.